Dampak perubahan tarif pph badan terhadap kinerja keuangan perusahaan telekomunikasi - Adina Syahidah; Nenden Kostini; Suryanto Suryanto (Keberlanjutan)
This study aimed to analyze the comparison between telecommunication companies’ financial performance before and after the changes in corporate income tax rates according to the Government Regulation in Lieu of Law No.1/2020. The research samples were obtained from four telecommunication companies listed on the Indonesia Stock Exchange (IDX) 2019-2020 through the purposive sampling method. The data was analyzed through Paired Sample t-Test and Shapiro-Wilk Test. This study indicated that the financial performance of telecommunication companies measured by the seven financial ratios (CR, DER, DAR, TATO, NPM, ROI, ROE) had insignificant differences between the changes in corporate income tax rates.